2006
DOI: 10.1016/j.molcel.2006.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of the p53 DNA-Binding Domain Regulates Apoptosis Induction

Abstract: The ability of p53 to induce apoptosis plays an important role in tumor suppression. Here, we describe a previously unknown posttranslational modification of the DNA-binding domain of p53. This modification, acetylation of lysine 120 (K120), occurs rapidly after DNA damage and is catalyzed by the MYST family acetyltransferases hMOF and TIP60. Mutation of K120 to arginine, as occurs in human cancer, debilitates K120 acetylation and diminishes p53-mediated apoptosis without affecting cell-cycle arrest. The K120R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
741
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 663 publications
(777 citation statements)
references
References 48 publications
35
741
0
1
Order By: Relevance
“…During this period, p53 may undergo a cascade of post-translational modifications including N-and C-terminal phosphorylations, C-terminal acetylation, sumoylation, methylation, ubiquitination and neddylation (Appella and Anderson, 2001;Brooks and Gu, 2003;Sykes et al, 2006). In particular, serines 15 and 37 act as substrates for DNA-PK and ATM following genotoxic stress (Vousden, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…During this period, p53 may undergo a cascade of post-translational modifications including N-and C-terminal phosphorylations, C-terminal acetylation, sumoylation, methylation, ubiquitination and neddylation (Appella and Anderson, 2001;Brooks and Gu, 2003;Sykes et al, 2006). In particular, serines 15 and 37 act as substrates for DNA-PK and ATM following genotoxic stress (Vousden, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…According to the charge neutralization model (Grunstein, 1997), acetylation of lysine residues would neutralize their positive charge and thus decrease the affinity of basic histones for the negatively charged DNA. This same mechanism could extend to an interaction between the basic tails of GST-pull down Sykes et al, 2006) Asterisks indicate the proteins that are also found in Drosophila MOF-containing complexes.…”
Section: H4k16ac In Chromatin Organizationmentioning
confidence: 91%
“…It is now known that MYST proteins have important roles in various biological processes (Ceol and Horvitz, 2004;Kusch et al, 2004;Dou et al, 2005;Smith et al, 2005;Mendjan et al, 2006;Sykes et al, 2006;Tang et al, 2006). These enzymes have been the subjects of several excellent reviews Squatrito et al, 2006;Avvakumov and Coˆte´, 2007;Lafon et al, 2007;Rea et al, 2007;Thomas and Voss, 2007).…”
Section: Identification Of Moz Morf and Other Mystic Hatsmentioning
confidence: 99%